2020
DOI: 10.1016/j.ajog.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Defining the relationship between vaginal and urinary microbiomes

Abstract: Background: Although the vaginal and urinary microbiomes have been increasingly wellcharacterized in health and disease, few have described the relationship between these neighboring environments. Elucidating this relationship has implications for understanding how manipulation of the vaginal microbiome may affect the urinary microbiome and treatment of common urinary conditions.Objective: To describe the relationship between urinary and vaginal microbiomes using 16S rRNA gene sequencing. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 32 publications
5
90
0
Order By: Relevance
“…While UTIs are curable by antibiotics, severe complications including pyelonephritis, haematuria, and chronic kidney disease (CKD) can cause permanent kidney damage [ 127 , 128 ]. Studies have shown that pathogens such as Gardnerella , Prevotella , and Ureaplasma potentially ascended from vaginal tract before causing infection in the urinary tract via the urethra and urinary bladder [ 129 131 ]. Vaginal dysbiosis has been shown to increase the risk of UTIs acquisition as compared to Lactobacillus -dominated vaginal microbiota [ 123 , 132 ].…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%
“…While UTIs are curable by antibiotics, severe complications including pyelonephritis, haematuria, and chronic kidney disease (CKD) can cause permanent kidney damage [ 127 , 128 ]. Studies have shown that pathogens such as Gardnerella , Prevotella , and Ureaplasma potentially ascended from vaginal tract before causing infection in the urinary tract via the urethra and urinary bladder [ 129 131 ]. Vaginal dysbiosis has been shown to increase the risk of UTIs acquisition as compared to Lactobacillus -dominated vaginal microbiota [ 123 , 132 ].…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%
“…There is a significant correlation between Lactobacillus colonization in the vagina and clinical outcomes (12,13,17). Lactobacillus, as the dominant bacterium, can balance the microbial flora of the genitourinary tract through a variety of mechanisms including host immune regulation, recovery of the vaginal flora, and interference with pathogen colonization (18,19). It is important for restoring the normal state of the flora and preventing infections and disease recurrence (9,18,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is debate as to whether the vaginal and urinary tract communities are distinct microbiota or if they are interconnected. 16S rRNA gene sequence studies have identified the same genera across the two sites [2,3]. Whole genome sequencing of vaginal and urinary tract isolates of the same species from the same individual suggests that the two microbiota are connected [4].…”
Section: Plos Onementioning
confidence: 99%
“…Lactobacilli are a prominent member of the healthy female urogenital tract [1]. 16S rRNA gene sequencing and shotgun whole genome sequencing of the vaginal and urinary tract microbiota have identified the same species in both niches, suggesting that the two microbiota are in fact interconnected [2][3][4]. The healthy vaginal microbiota is often dominated by one of four Lactobacillus species: Lactobacillus crispatus, L. iners, L. gasseri, or L. jensenii [5,6].…”
Section: Introductionmentioning
confidence: 99%